Sensory assessment of balance regulation of physically active women, 60-79 years old - Marcelo de Maio Nascimento; Paloma Sthefane Teles Silva (Brazilian Society of Geriatrics and Gerontology, 2021)
OBJECTIVE: To evaluate the performance of sensory regulation of static and dynamic balance in older women, and to verify the sensitivity and specificity levels of the Body Balance Test (Teste de Equilíbrio Corporal, TEC) in relation to its reference standard, determining the best cutoff point for identifying risk of falling. METHODS: 74 women (age 67.59 ± 5.26 years) participated in the study, divided into fallers (n = 18) and non-fallers (n = 56). RESULTS: Comparatively, non-fallers had higher performance scores on static balance exteroceptive regulation (SBER), dynamic balance exteroceptive regulation (DBER), and dynamic balance interoceptive regulation (DBIR). Statistically significant differences were found in DBER (p = ≤0.001) and DBIR (p = 0.031). The area under the ROC curve was 0.73 (95%CI 0.58 - 0.88; p = 0.003), with a sensitivity level of 42.30% and specificity of 84.80%. CONCLUSIONS: The greatest chance of falling was found for dynamic balance in situations of exteroceptive and interoceptive regulation for older women with and without a history of falls. Deficits in sensory regulation of body balance are common in older women, both fallers and non-fallers.